Efeito do laser de baixa potência sobre células musculares c2c12 submetidas à lesão por miotoxinas BTHTX - I e BTHTX - II isoladas do veneno da serpente bothrops jararacussu - Santos, Adriano Silvio dos (2015)
Snakes venom of the Bothrops species induces a local inflammatory reaction, characterized by pain, edema, leukocyte migration and can be accompanied by tissue necrosis. The use of antivenom performs the function of neutralizing the greatest possible amount of circulating venom, thus minimizing its systemic effects, but its action does not extend to local manifestations, and thus require the use of another therapeutic option to control this reaction. The low level laser therapy (LLLT) is used as an alternative treatment in cases of muscle injury due to its biological effects, such as analgesics, anitinflamatory and healing. In a previous study of our lab it was found that LBP can enhance the viability of C2C12 muscle cells after the addition of B. jararacussu venom in the medium and that this effect of LBP is related to protection of the cell membrane. In the present study we analyzed the effect of LBP in the cell monolayer integrity, viability of muscle cells, exposed to injury by myotoxins BthTX - I - and BthTX - II isolated from Bothrops jararacussu venom. Cells received BthTX – I (75 μg / mL) and were immediately irradiated with LLLT Aluminum Indium Gallium Phosphate and Aluminium Gallium Arsenide, the wavelengths (λ) 685nm and 830 nm, power density 4 J/cm2, 100mW of power, total energy 1,3 J, application time of 13 and 35 seconds per point and the cells were incubated for 15, 30 and 60 minutes. The results demonstrated that BthTX – I affect cell viability in a dose dependent manner, but did not change cell integrity. The concentration of 75 μg/mL was chosen for the experiments with LBP. LLLT caused an significant increase in cell viability in all the analyzed period of time and in the λ 685 nm and 830 nm against Bothrops I toxin, however in the LBP λ 685 nm against Bothrops toxin II was effective only at 15 min, while the LBP at λ 830 was effective at 15 and 60 min. The LLLT was not able to change the LDH release at all times and wavelength used. Thus, LBP was able to protect C2C12 muscle cells against the miotoxic effect of isolated myotoxins isolated from B. jararacussu venom. Therefore, the results suggest that LLLT can be considered an effective therapeutic tool in patients bitten by snakes.